An A to Z of monsters and magical beings - Onn, Aidan (Laurence King Publishing, 2017)
Do you know how to escape from a stalking werewolf? Have you always wanted to learn the difference between a hobgoblin and an imp, and do you know the secret to avoiding the sharp claws of the ancient Eloko monster? Learn all these brilliant facts and more with this guide to the strange, scary and wonderful world of monsters and ancient mythical beings!
Keywords: Imaginary creatures / Juvenile literature; Monsters / Juvenile literature; Animals, Mythical / Juvenile literature; Monsters; Animals, Mythical; Imaginary creatures; JUVENILE NONFICTION / Humor; JUVENILE NONFICTION / Social Science / Folklore & Mythology; Juvenile works; Picture books; Children's nonfiction; Bilderbuch